Teologi Keselamatan Injil Lukas 19:1-10 dan Relevansinya Bagi Pendidikan Agama Kristen - Hasudungan Sidabutar; Rinto Hasiholan Hutapea (Sekolah Tinggi Theologia Nazarene Indonesia, 2020)
This study explores the concept of salvation. The study aims to answer the problem of differences in the concept of safety that students have in schools. The research method used in this research is qualitative research with a literature approach. The results of the research are as follows: First, the salvation of the Old Testament to the New Testament is the salvation of God Himself. Second, man is not saved by his own efforts but rather the Work of God, who is active in the work of salvation. Third, the Gospel of Luke contains a universal theology of salvation. Fourth, salvation does not look at boundaries, but salvation from God through Jesus Christ breaks through the boundaries made by humans. Fifth, human judgment is not the determinant of salvation but only God Himself should place it. Sixth, the concept of salvation in the Gospel of Luke 19: 1-10 can be considered in Christian Religious Education learning materials in schools.